Kimberly Maslin: The Experiential Ontology of Hannah Arendt, Lanham/Boulder/New York: Lexington Books 2022. : Being-with Others in Liberal Democracies: Heidegger, Arendt and Identity Politics - Yechezkel, Ayal (HannahArendt.net, 2022)
Touching some of the most important questions in the scholarly study of Hannah Arendt’s political thought, Maslin’s The Experiential Ontology of Hannah Arendt is an attempt not only to tell the story of Arendt’s debt to her teacher from the University of Marburg but to illustrate the importance of reading both thinkers for the present political situation in liberal democracies. In this way, Maslin’s book takes us on a journey beyond both Heidegger and Arendt and asks us to try to think together, with others and with ourselves, the meaning of our Being through our own experience of the world.